Banking Financial Performance, Inflation Level, Bank Indonesia Interest Rate, and Economic Growth in Indonesia - Maratus Zahro; Mega Arisia Dewi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
This study aimed to test the effect of bank financial performance, inflation rates, Bank Indonesia interest rates on economic growth in Indonesia. This type of research was quantitative. The research sample consisted of 87 conventional banks and 12 Islamic banks during 2015-2017 as samples. The sampling technique used was purposive sampling method, sampling technique using certain criteria. The analytical method of this study used multiple linear regression analysis technique. The results showed that (a) financial performance which is proxied by CAR, BDR, and LDR of conventional banks has no effect on economic growth in Indonesia, (b) financial performance which is proxied by ROA has a positive effect on economic growth in Indonesia, (c) proxied financial performance with CAR, BDR, FDR, and ROA of Islamic banks have no effect on economic growth in Indonesia, (d) inflation has a positive effect on economic growth in Indonesia, (e) interest rates in Indonesia have a negative effect on economic growth in Indonesia.